1996
DOI: 10.1056/nejm199607183350302
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Resection for the Treatment of Menorrhagia

Abstract: Endometrial resection is an effective alternative to hysterectomy in women with menorrhagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
64
4
14

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(90 citation statements)
references
References 25 publications
8
64
4
14
Order By: Relevance
“…Resection of endometrium procedure is a safe and effective in selected patients and most women undergoing resection of endometrium will avoid hysterectomy [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Resection of endometrium procedure is a safe and effective in selected patients and most women undergoing resection of endometrium will avoid hysterectomy [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Hysteroscopic ablation has resulted in high success rates of 75-100% (mean 85%) [6,7,8,9,10,11]. These methods are skill dependent, require intensive training and expertise, and are not free of complications such as perforation, hemorrhage, visceral injury, and excessive fluid overload absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Transcervical endometrial resection (TCRE) has been shown to be an effective and safe method for treating DUB [43]. TCRE was tested in nonrandomized prospective studies, which reported a satisfaction rate between 85% and 87% and an amenorrhea rate varying up to 46% (Table 2) [44,45]. TCRE is comparable to other hysteroscopic endometrial ablation techniques in terms of amenorrhea and satisfaction rates [46,47].…”
Section: First-generation Endometrial Ablation Techniquesmentioning
confidence: 99%